Legal Aspects of Indonesia's Obligation to Use Renewable Energy - Imawan, Riswandha; Rehulina, Rehulina (Faculty of Law, Jambi University, 2022)
The continued use of fossil fuel energy can increase the concentration of CO₂ gas in the atmosphere and is a major cause of climate change. Amid concerns about the impact of fossil fuel energy use, fossil fuels still dominate national energy consumption in Indonesia. In this position, it is important to know how the legal aspects related to Indonesia's obligations in the utilization of natural resources, especially in encouraging the use of renewable energy. This research is a normative juridical research. This research aims to analyze what legal aspects provide an obligation for Indonesia to make an energy transition. This is important to encourage the use of renewable energy in Indonesia. The results of this study show that Indonesia has an obligation to encourage the use of renewable energy, where this obligation arises from aspects of national law and from aspects of international law